Linking brand engagement to customer-based brand equity and role of brand experience, brand personality, and brand affect: A case of automobile market of Pakistan - Kashif Farhat; Sany Sanuri Mohd Mokhtar; Salniza Bt Md. Salleh (Management Science Letters, 2020)
Brand engagement is relatively a new concept in marketing. The objective of this research study is to unearth the relationship between brand engagement and customer-based brand eq-uity drivers; brand personality, brand experience, and brand affect. The data was collected from 426 automobile customers in Pakistan through multi-stage cluster sampling technique. The PLS-SEM analysis of the data supported the relationships between brand equity drivers and brand engagement and the mediating role of brand affect. Brand experience, brand personality, and brand affect emerged significant predictors to brand engagement behavior of the automobile customers. It is recommended for the brand managers to design marketing plans that emphasize the pleasant brand experience which results in brand affect, ultimately leading to brand engagement behavior.